VD_FINDINFO HC / 2016 / 216 vom 29. Februar 2016 - VD Tribunal cantonal (2016)
TRANSACTION JUDICIAIRE, FRAIS JUDICIAIRES, DÉPENS, ASSISTANCE JUDICIAIRE | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)